Interest Rate Pass-Through: The Case of Indonesia - Chandra Utama; Rizqianisa Septiani (Faculty of Economic and Business Syarif Hidayatullah State Islamic University of Jakarta, 2017)
This paper examines the direct and indirect interest rate pass-trough (IRPT) from policy interest rate (BI rate) to banks’ retail interest rates in Indonesia during a full-fledged inflation-targeting regime. We use montly data of policy interest rate (BI rate) as well as interest rates for interbank money market (interbank), deposit, and loan during July 2005 to May 2015. We employ Error Correction Mechanism (ECM) and Ordinary Least Square (OLS) to find the significant of IRPT and the speed of adjustment process of IRPT. The study suggests the existence of direct and indirect IRPT in Indonesia. The change of policy rate is transmitted quicker in the direct channel compared to the indirect channel. However, indirect channel is more stable than the direct channel. We conclude that the direct and indirect IRPT are complementary.DOI: 10.15408/sjie.v6i2.4819